Budget by Result and Its Incidence on The Quality of Public Spending Management, in the City of Chincha 2021 - Gutierrez, Etheel Romila Becerra; Nuñez, Freddy Jhonny Sachun; Cabrejos, Ruth Gissela Perez; Kevin Frederick Sachun Becerra (South Eastern European Journal of Public Health, 2024)
The purpose of this study was to clarify the relationship between economic performance and the quality of public spending in the city of Chincha in the year 2021. This study used a non-experimental, cross-sectional, descriptive, causal design with a quantitative approach. The sample consisted of 60 government officials from the Chincha health sector. The data collection technique was used, questionnaires as tools to evaluate these two variables. The value of Nagelkerke's pseudo R2 (0.346) depends on 34.6% of the uncertainty related to the quality of the administration costs. public finance. by results Indicators measure the amount and rate of spending, limited skills, the persistence of corruption, financial allocation performance, and evidence of a narrow health gap, rather than the quality of spending that the industry does not it can be better.rea.